John Murtagh's practice tips - Murtagh, John, 1936- (McGraw-Hill Education, 2013)
Provides essential information and step-by-step instructions on how to deal with conditions encountered by GPs around the world. This title provides tried-and-tested approaches to treatment and improvisation methods, using convenient tools and readily available equipment to treat patients as effectively as possible.